Decentralized control for spacecraft formation in elliptic orbits. Issue 1 (2nd January 2018) - Wu, Baolin; Cao, Xibin
Abstract : Purpose: This paper aims to address the problem of formation control for spacecraft formation in elliptic orbits by using local relative measurements. Design/methodology/approach: A decentralized formation control law is proposed to solve the aforementioned problem. The control law for each spacecraft uses only its relative state with respect to the neighboring spacecraft it can sense. These relative states can be acquired by local relative measurements. The formation control problem is converted to n stabilization problems of a single spacecraft by using algebraic graph theories. The resulting relative motion model is described by a linear time-varying system with uncertain parameters. An optimal guaranteed cost control scheme is subsequently used to obtain the desired control performance. Findings: Numerical simulations show the effectiveness of the proposed formation control law. Practical implications: The proposed control law can be considered as an alternative to global positioning system-based relative navigation and control system for formation flying missions. Originality/value: The proposed decentralized formation control architecture needs only local relative measurements. Fuel consumption is considered by using an optimal guaranteed cost control scheme.